PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENYELUDUPAN MANUSIA DARI DAN LUAR INDONESIA - Saputra, Dodi Ripo; Harahap, Irawan; Triana, Yeni (LPPM STIH Awang Long, 2024)
Immigration in Indonesia is regulated by Law Number 6 of 2011 on Immigration, which replaced the previous immigration law, Law Number 9 of 1992. The law states that anyone who enters or exits Indonesia without undergoing immigration inspection, or without valid travel documents or visas, will be subject to criminal sanctions. The legal foundation for human trafficking offenses is also outlined in Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers. Immigration matters are closely related to the movement of people across international borders, which has increased in the era of globalization and free trade, and has now become a concern for countries around the world, including Indonesia. Smuggling, which involves trafficking people for exploitation or physical and psychological abuse, is a violation of human dignity. The method used in this research is sociological legal research. Based on the results, it is known that law enforcement at the Bengkalis Immigration Checkpoint Office (TPI) is in accordance with the provisions set out in the Immigration Law. However, challenges remain, such as limited human resources, inadequate infrastructure, and suboptimal coordination between agencies. Handling human trafficking requires active involvement from various parties, including the police, customs, and other related agencies, to strengthen oversight and prevent this transnational crime. This research concludes that to improve the effectiveness of law enforcement, there needs to be enhanced training for officers, improvement of inspection facilities and infrastructure, and strengthened cooperation between agencies involved in the prevention and prosecution of human trafficking. Additionally, a broader socialization to the public regarding the dangers and impacts of human trafficking should also be conducted to strengthen preventive efforts.